Potential of marine sponge-derived fungi in the aquaculture system - Muhammad Syaifudien Bahry; Ocky Karna Radjasa; AGUS TRIANTO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Bahry MS, Radjasa OK, Trianto A. 2021. Potential of marine sponge-derived fungi in the aquaculture system. Biodiversitas 22: 2883-2892. Organic waste from aquaculture is one of the triggers of disease outbreaks and a decrease in water quality that urgently needs to be resolved. Indonesia has a high diversity of sponges including their associated microorganisms that potential in the field of biotechnology. This study aimed to determine the enzymatic and anti-vibrio activity of fungi associated with marine sponges and identify potential fungi. The specimen of sponges was collected from Samalona Island, South Sulawesi, Indonesia. The enzymatic and anti-vibrio assay was conducted by using the plug method and the activity was determined by a clear zone around the fungal isolates. Fungal identification was carried out molecularly using universal primers ITS1 and ITS4 and phylogenetic tree analysis. The fungal isolates were screened for the extracellular enzyme activity (amylase, cellulase, protease) and anti-vibrio activity against Vibrio parahaemolyticus, V. harveyi, and V. vulnificus). A total of three fungal isolates have been isolated from the sponge Monanchora sp. Isolate SL 3 SP 3.3 had potential enzymatic activities with Enzymatic Indeks (EI) 3.95±0.17 on amylase, 3.75±0.36 on cellulase, 5.38±0.30 on protease. The highest anti-vibrio activity was obtained against V. harveyi with an inhibition zone diameter of 4.82 ±0.37 mm. The results of fungal identification showed that isolate SL3SP3.3 had a sequence length of 638 bp and was closely related to Trichoderma reesei a.k.a Hypocrea jecorina with a similarity value of 99.69%.